Analisis Penyelenggaraan Makanan Di Instalasi Gizi RSUD Besemah Pagar Alam Tahun 2021 - Reny Sartika; Lilis Suryani; Atma Deviliawati (Jurnal Kesehatan Saelmakers PERDANA, 2022)
According to the Minister of Health Regulation Number 7 of 2019 concerning the health of the hospital environment, ready-to-eat food in hospitals is all food and drinks served from the hospital kitchen for patients and employees, as well as food and drinks sold within the hospital environment. This study aims to obtain in-depth information about food administration from the aspect of the process (planning, procurement, receipt, storage, processing and distribution of food) at the nutrition installation of Besemah Pagar Alam Hospital in 2021. The type of research used is a qualitative descriptive study with a phenomenological approach with technical techniques. interviews of informants or direct sources and secondary data with 9 respondents. This research was conducted on 5 – 20 July 2021. Data were collected using recording, then the data that had been carried out was analyzed. The results of this study on the process aspect of planning obtained information that aspects of the food ingredient planning process were not in accordance with PGRS guidelines. Then the process aspect of the procurement of foodstuffs includes ordering and purchasing foodstuffs, information is obtained that the procurement activities of foodstuffs are guided by PGRS. In the process aspect of receiving food ingredients, information was obtained that the activities of receiving food ingredients were not in accordance with PGRS guidelines. In the aspect of the food storage process, information was obtained that the storage of foodstuffs was not in accordance with the standards in the PGRS. In the process aspect of food processing, information is obtained that the food processing activities have been carried out according to the prerequisites of the PGRS guidelines, namely the availability of menus, menu guidelines, menu cycles, food ingredients to be cooked, cooking utensils, cooking assessments, availability of cooking SOPs, and regulations. use of food additives. In the process aspect of food distribution, information was obtained that the food distribution activities were not in accordance with PGRS guidelines.